The incidence and management of moderate to severe head injury (08.03.2019) - Maegele, Marc; Unterberg, Andreas (Deutsches Ärzteblatt, 2019)
Traumatic brain injury (TBI) remains one of the major medical and socioeconomic challenges of our time (1-4). In 2016, 419 507 patients were hospitalized for TBI of all grades of severity (ICD-10 S00-S09: injuries to the head) in Germany alone (5)....
Gesehen am 12.06.2019